Effects of side-effect risk framing strategies on COVID-19 vaccine intentions: a randomized controlled trial - Nikkil Sudharsanan; Caterina Favaretti; Violetta Hachaturyan; Till Bärnighausen; Alain Vandormael (eLife, 2022)
Background: Fear over side-effects is one of the main drivers of COVID-19 vaccine hesitancy. A large literature in the behavioral and communication sciences finds that how risks are framed and presented to individuals affects their judgments of its severity. However, it remains unknown whether such framing changes can affect COVID-19 vaccine behavior and be deployed as policy solutions to reduce hesitancy. Methods: We conducted a pre-registered randomized controlled trial among 8998 participants in the United States and the United Kingdom to examine the effects of different ways of framing and presenting vaccine side-effects on individuals’ willingness to get vaccinated and their perceptions of vaccine safety. Results: Adding a descriptive risk label (‘very low risk’) next to the numerical side-effect and providing a comparison to motor-vehicle mortality increased participants’ willingness to take the COVID-19 vaccine by 3.0 percentage points (p=0.003) and 2.4 percentage points (p=0.049), respectively. These effects were independent and additive and combining both framing strategies increased willingness to receive the vaccine by 6.1 percentage points (p<0.001). Mechanistically, we find evidence that these framing effects operate by increasing individuals’ perceptions of how safe the vaccine is. Conclusions: Low-cost side-effect framing strategies can meaningfully affect vaccine intentions at a population level. Funding: Heidelberg Institute of Global Health. Clinical trial number: German Clinical Trials Registry (#DRKS00025551).